Transplantation of Neural Stem Cells Cotreated with Thyroid Hormone and GDNF Gene Induces Neuroprotection in Rats of Chronic Experimental Allergic Encephalomyelitis. (10th January 2016) - Gao, Xiaoqing; Hu, Guangqiang; Deng, Li; Fan, Guangbi; Yang, Chaoxian; Du, Jie
Abstract : The present study investigates whether transplantation of NSCs treated with T3 alone (T3/NSCs), or in conjunction with GDNF gene (GDNF-T3/NSCs), provides a better therapeutic effect than NSCs for chronic EAE. EAE rats were, respectively, injected with NSCs, T3/NSCs, GDNF-T3/NSCs, and saline at 10 days and sacrificed at 60 days after EAE immunization. The three cell grafted groups showed a significant reduction in clinical scores, inflammatory infiltration, and demyelination compared with the saline-injected group, and among the cell grafted groups, the reduction in GDNF-T3/NSCs group was the most notable, followed by T3/NSCs group. Grafted T3/NSCs and GDNF-T3/NSCs acquired more MAP2, GalC, and less GFAP in brain compared with grafted NSCs, and grafted GDNF-T3/NSCs acquired most MAP2 and least GalC among the cell grafted groups. Furthermore, T3/NSCs and GDNF-T3/NSCs grafting increased the expression of mRNA for PDGF α R, GalC, and MBP in lesion areas of brain compared with NSCs grafting, and the expression of mRNA for GalC and MBP in GDNF-T3/NSCs group was higher than that in T3/NSCs group. In conclusion, T3/NSCs grafting, especially GDNF-T3/NSCs grafting, provides a better neuroprotective effect for EAE than NSCs transplantation.